Contact angle measurement for LiBr aqueous solutions on different surface materials used in absorption systems. (November 2018) - Martinez-Urrutia, Asier; Fernandez de Arroiabe, Peru; Ramirez, Miguel; Martinez-Agirre, Manex; Mounir Bou-Ali, M.
Highlights: Contact angle of the aqueous LiBr solution on different materials are presented. Contact angle – Solution surface linear relation is observed in all materials. Three Metals show a hygrophilic performance, while PTFE showed hygrophobic one. An estimation of the minimum wetting rate has been performed by obtained results. The contact angle should be considered in LiBr–H2 O components analysis and design. Abstract: Wetting surface is a very important issue for the design of absorption applications and heat exchangers. The contact angle is deemed essential in wettability studies; However, LiBr aqueous solution contact angle studies are limited. This work analyses the contact angle of LiBr aqueous solution in the range of 0–55% mass fraction on different material surfaces: copper, aluminum, stainless-steel and polytetrafluoroethylene (PTFE) under atmospheric conditions. A sessile drop technique was used for measuring the contact angles, and a linear relation between solution surface tension and contact angle is observed in the tested materials. The study of three metals show hydrophilic performance ( θ < 90°), whereas the PTFE shows hydrophobic performance. Additionally, the effect of the selection of the material, and consequent effect on the contact angle, on the minimum wetting rate and film thicknesses is presented under the working conditions of the absorption technologies. From the wettability point of view, the results show that using stainless-steel and aluminum leads to a slightly better performance than a copper made heat exchanger.